The Relationship between Coffee Consumption and Hypertension in the Elderly - Yuliana, Erlimia Eka Noor; Susanto, Agung; Hanim, Diffah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Coffee contains many potentially active compounds such as caffeine, chlorogenic acids, trigonellin, magnesium, etc. that affect health. Effect of coffee consumption and hypertension is still not known with certainty because of differences in the results of existing research. Therefore, this study aimed to determine the relationship between coffee consumption and hypertension. Methods: This study was conducted with a cross-sectional study of the 103 elderly in Ngudi Sehat Elderly IHC, Surakarta. Samples obtained from the total sample with inclusion and exclusion criteria (n = 90). Independent variable data that is amount and type of coffee consumption obtained from interviews. While the variable dependet taken by measuring blood pressure and categorize by JNC VII. Data were tested with the non-parametric Spearman correlation test and ordinal regression test (Î± <0.05). Results: The results of the Spearman correlation test showed no significant correlation between the amount of coffee consumption and hypertension (p = 0.432) as well as the type of coffee and hypertension (p = 0.668) in the elderly. Meanwhile, the results of ordinal regression test showed variable that significant influences hypertension are age and body mass index. Conclusion: There is no relationship between coffee consumption and hypertension in the elderly. Elderly with hypertension is recommended to live a healthy lifestyle such as maintaining body weight with physical activity, stop smoking and maintaining intake of nutrient. Keywords: coffee, caffeine, hypertension, elderly, blood pressure